Hydrogen Production from Winery Wastewater Through a Dual-Chamber Microbial Electrolysis Cell - Ana Baía; Alonso I. Arroyo-Escoto; Nuno Ramos; Bilel Abdelkarim; Marta Pereira; Maria C. Fernandes; Yifeng Zhang; Annabel Fernandes (Energies)
This study explores the feasibility of producing biohydrogen from winery wastewater using a dual-chamber microbial electrolysis cell (MEC). A mixed microbial consortium pre-adapted to heavy-metal environments and enriched with Geobacter sulfurreducens was anaerobically cultivated from diverse waste streams. Over 5000 h of development, the MEC system was progressively adapted to winery wastewater, enabling long-term electrochemical stability and high organic matter degradation. Upon winery wastewater addition (5% v/v), the system achieved a sustained hydrogen production rate of (0.7 ± 0.3) L H2 L−1 d−1, with an average current density of (60 ± 4) A m−3, and COD removal efficiency exceeding 55%, highlighting the system’s resilience despite the presence of inhibitory compounds. Coulombic efficiency and cathodic hydrogen recovery reached (75 ± 4)% and (87 ± 5)%, respectively. Electrochemical impedance spectroscopy provided mechanistic insight into charge transfer and biofilm development, correlating resistive parameters with biological adaptation. These findings demonstrate the potential of MECs to simultaneously treat agro-industrial wastewaters and recover energy in the form of hydrogen, supporting circular resource management strategies.